QSAR Analysis of Benzothiazole Derivatives of Antimalarial Compounds Based On AM1 Semi-Empirical Method - Ruslin Hadanu; Salim Idris; I Wayan Sutapa (Universitas Gadjah Mada, 2015)
Quantitative Structure and Activity Relationship (QSAR) analysis of 13 benzothiazoles derivatives compound as antimalarial compounds have been performed using electronic descriptor of the atomic net charges (q), dipole moment (μ), ELUMO, EHOMO and polarizability (α). The electronic structures as descriptors were calculated through HyperChem for Windows 7.0 using AM1 semi-empirical method. The descriptors were obtained through molecules modeling to get the most stable structure after geometry optimization step. The antimalarial activity (IC50) were taken from literature. The best model of QSAR model was determined by multiple linear regression approach and giving equation of QSAR: Log IC50 = 23.527 + 4.024 (qC4) + 273.416 (qC5) + 141.663 (qC6) – 0.567 (ELUMO) – 3.878 (EHOMO)– 2.096 (α). The equation was significant on the 95% level with statistical parameters: n = 13, r = 0.994, r2 = 0.987, SE = 0.094, Fcalc/Ftable = 11.212, and gave the PRESS = 0.348. Its means that there were only a relatively few deviations between the experimental and theoretical data of antimalarial activity.